V-type crystal formation in starch by aqueous ethanol treatment: The effect of amylose degree of polymerization. (December 2016) - Dries, D.M.; Gomand, S.V.; Delcour, J.A.; Goderis, B.
Abstract: Maize, rice, cassava, potato and pea granular starches, representing the different starch polymorphs (A-, B- and C-types) and covering a broad range in amylose (AM) content and degree of polymerization (DP), were converted to VH -type granular starch by aqueous ethanol treatment at 95 °C in a 68 to 48% ethanol (v/v) range. Microscopy, X-ray diffraction and calorimetric analyses showed that loss of native molecular order already occurred at the highest ethanol concentrations for starches containing the intrinsically less stable B-type crystals, whereas lower ethanol concentrations were necessary to induce native crystal melting in A-type starches. C-type starch, containing a mixture of A- and B-type crystals, exhibited features characteristic of both A- and B-type starches. No native crystals remained and granular products containing only VH -type crystals were formed for all starches when using 48% (v/v) ethanol. However, the relative kinetics of VH -type crystal formation depended on AM DP. For low DP AM starches (maize and rice), VH -type crystal formation started during heating up to 95 °C once the native crystals were melting. The VH -type crystallization went up to completion during the isothermal stay at 95 °C. For mid (pea) and high DP (potato and cassava) AM starches, VH -type crystallization was initiated during holding at 95 °C and progressed further during subsequent cooling. The VH -type crystallinity in the final product decreased with increasing DP of the AM fraction, likely as a result of progressively more disturbing entanglements. Surprisingly, there was no quantitative relation between VH -type crystallinity and AM content. Graphical abstract: Highlights: Native A-, B- and C-type starches are converted into VH -type granular starches. Starches in aqueous ethanol are heated to and held at 95 °C prior to cooling. B-type crystals are inherently less stable in ethanolic media than A-type crystals. Kinetics of VH -type crystal formation depended on amylose degree of polymerization. Amylose content and VH -type crystallinity of converted starches are not related.